Interdisciplinary Approaches in Teaching English to Technical Students - Khamdamova , Sevarakhon (The Lingua Spectrum, 2024)
This article discusses the importance of interdisciplinary approaches in teaching English to technical students, emphasizing how these methods can enhance engagement, practical application, critical thinking, and collaboration skills. It identifies key benefits, such as increased motivation and real-world relevance, while also addressing challenges like resistance to change and resource limitations. The article proposes strategies for successful implementation, including collaborative curriculum design, project-based learning, professional development for educators, and comprehensive assessment methods. Overall, it advocates for a more integrated approach to language learning that prepares students for success in a globalized workforce.